Routine Childhood Immunization: Its health, developmental, economic and social benefits - Sangma, Risa Vernette Nengminza; Rasania, Sanjeev Kumar; Vijayan, Sruthi Madathiparambil; Mishra, Pallavi; Chawale, Shubham Vivekanand (Indian Journal of Community Health, 2023)
Introduction: Immunization plays a pivotal role in public health. It is one of the most cost-effective inventions that have helped bring down a significant amount of burden of diseases among under-five children, some of which are now on the verge of extinction. Objective: To assess the diverse benefits of routine childhood immunization. Methodology: A literature review was conducted using electronic database to understand the broader benefits of immunization. Results: Studies have shown that routine childhood immunization have been able to reduce the incidence of influenza and other targeted diseases (diphtheria, Haemophilus influenzae type b, measles, mumps, polio, and rubella) by 17% and 100% respectively. Conclusion: Vaccines are known to have protective and positive health benefit which extends beyond infancy and childhood. It is therefore one of the best strategies in public health to reduce morbidity and mortality and enable child survival.